Effect Of Sleep Hygiene And Deep Breathing Exercise With Spiritual Care On Sleep Quality And Quality Of Life Of Hemodialysis Patient In Ahmad Yani Islamic Hospital Surabaya - Siti Nur Hasina; Tintin Sukartini; Eppy Setiyowati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2018)
Hemodialysis patients experienced sleep disturbance problems that directly affect sleep quality and quality of life of hemodialysis patients. Quality of life is an important part of hemodialysis patients that need attention. The purpose of this study was to analyze the effect of sleep hygiene and deep breathing exercise with spiritual care on sleep quality and quality of life of hemodialysis patients. The research design used a quasy experiment with the pretest posttest approach with control group. Population in this study were all of hemodialysis patients . Sample of this study were 38 respondents divided into 19 respondents for intervention group and 19 respondents for control group. Sleep hygiene intervention and deep breathing exercise with spiritual care were applied every day for 30 days 30 minutes before going to sleep in the intervention group and in the control group only ran routine or habit before going to bed. Instrument used a PSQI questionnaire (Pittsburgh Sleep Quality Index) and KDQOL SFTM 1.3 (Kidney Disease Quality of Life). Data analysis used MANOVA test with significance value α = 0.05. The results of this study indicated that p value 0,000 with the effect of R squared 72.7% on sleep quality and 66.4% on quality of life, which means that sleep hygiene and deep breathing exercise with spiritual care were significantly influence sleep quality and quality of life on hemodialysis patient in Ahmad Yani Islamic Hospital Surabaya. The application of sleep hygiene and deep breathing exercise with spiritual care had a strong influence on the quality of sleep and the quality of life of hemodialysis patients. Nurses are expected to be able to implement sleep hygiene interventions and deep breathing exercises with spiritual care to enhance sleep quality and quality of life for hemodialysis patients. Keyword        : Hemodialysis, Sleep Quality, Quality of Life, Sleep Hygiene, Deep Breathing Exercise, Spiritual care